The cold circumgalactic medium in emission: Mg ii haloes in TNG50. Issue 3 (29th July 2021) - Nelson, Dylan; Byrohl, Chris; Peroux, Celine; Rubin, Kate H R; Burchett, Joseph N
ABSTRACT: We outline theoretical predictions for extended emission from Mg ii, tracing cool ∼10 4 K gas in the circumgalactic medium (CGM) of star-forming galaxies in the high-resolution TNG50 cosmological magnetohydrodynamical simulation. We synthesize surface brightness maps of this strong rest-frame ultraviolet metal emission doublet (λλ2796, 2803), adopting the assumption that the resonant scattering of Mg ii can be neglected and connecting to recent and upcoming observations with the Keck/KCWI, VLT/MUSE, and BlueMUSE optical integral field unit spectrographs. Studying galaxies with stellar masses 7.5 < log ( M ⋆ / M ⊙ ) < 11 at redshifts z = 0.3, 0.7, 1, and 2 we find that extended Mg ii haloes in emission, similar to their Ly α counterparts, are ubiquitous across the galaxy population. Median surface brightness profiles exceed 10 −19 erg s −1 cm −2 arcsec −2 in the central 10 s of kpc, and total halo Mg ii luminosity increases with mass for star-forming galaxies, reaching 10 40 erg s −1 for M ⋆ ∼ 10 9.5 M⊙ . Mg ii halo sizes increase from a few kpc to ≳ 20 kpc at the highest masses, and sizes are larger for haloes in denser environments. Mg ii haloes are highly structured, clumpy, and asymmetric, with isophotal axial ratio increasing with galaxy mass. Similarly, the amount and distribution of Mg ii emission depends on the star formation activity of the central galaxy. Kinematically, inflowing versus outflowing gas dominates the Mg ii luminosity at high and low galaxy masses, respectively, although the majority of Mg ii halo emission at z ∼ 0.7 traces near-equilibrium fountain flows and gas with non-negligible rotational support, rather than rapidly outflowing galactic winds.